Agronomic and yield performances of cucumber [Cucumis sativus] on soil amended with different rates of cattle manure in derived savannah Agroecological zone of Ondo state, Nigeria - Eleduma Ajayi Festus (Open Journal of Plant Science - Peertechz Publications, 2023)
Most soils have experience nutrient depletion as a result of long-term farming, making good yields only possible with the application of fertilizers. A Randomized Complete Block Design (RCBD) was used to create a total of fifteen (15) plots in the study, which was conducted at the Rufus Giwa Polytechnic's Teaching Research and Commercial Farms in Owo, Ondo State, Nigeria. The study examined the impact of various rates of cattle manure on cucumber. The results revealed that the performance of cucumbers was significantly impacted by an increase in the rate of cattle manure, with 15 tha-1 of cattle manure producing the best results in terms of growth and yield (3.45 cm, 73.46 cm, 171.22 cm2, 16.83, 9.83 cm, 21.89 cm, 17.19 cm, and 5.14 kg as stem girth, vine length, leaf area, number of leaves, number of fruits, fruit weight, and fruit circumference) and the lowest from control. According to the study, applying cattle manure in the study area at a rate of 15 tha-1 considerably improves cucumber growth and yield. In order to improve the physical and chemical properties of the soil and eliminate the need to apply inorganic fertilizer, farmers in the research area are advised to amend their soils with 15 tha-1 cattle dung.